2010
DOI: 10.1007/s00445-010-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

First 13C/12C isotopic characterisation of volcanic plume CO2

Abstract: We describe analytical details and uncertainty evaluation of a simple technique for the measurement of the carbon isotopic composition of CO 2 in volcanic plumes. Data collected at Solfatara and Vulcano, where plumes are fed by fumaroles which are accessible for direct sampling, were first used to validate the technique. For both volcanoes, the plume-derived carbon isotopic compositions are in good agreement with the fumarolic compositions, thus providing confidence on the method, and allowing its application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 67 publications
(66 reference statements)
3
44
1
Order By: Relevance
“…The assimilation of carbonate rocks belonging to the sedimentary basement is a further possible mechanism affecting C isotopes. This process has been already identified at Mt Vesuvius and other volcanoes in Central Italy on the basis of petrological constraints (Iacono-Marziano et al, 2009), and it has also been proposed that it occurs at Mt Etna (Chiodini et al, 2010). Future petrological studies will have to quantify the effective degree of carbonate assimilation experienced by Mt Etna magmas.…”
Section: Final Remarks and Inferences About The Plumbing Systemmentioning
confidence: 80%
“…The assimilation of carbonate rocks belonging to the sedimentary basement is a further possible mechanism affecting C isotopes. This process has been already identified at Mt Vesuvius and other volcanoes in Central Italy on the basis of petrological constraints (Iacono-Marziano et al, 2009), and it has also been proposed that it occurs at Mt Etna (Chiodini et al, 2010). Future petrological studies will have to quantify the effective degree of carbonate assimilation experienced by Mt Etna magmas.…”
Section: Final Remarks and Inferences About The Plumbing Systemmentioning
confidence: 80%
“…However, in a recent study, it has been suggested that the carbon isotope variations in degassed volcanic CO 2 at Mt. Etna could be due to carbonate assimilation (Chiodini et al, 2011). While the petrological implications of magma-carbonate interaction processes is not the goal of this study, when mantle-derived melts interact with the crust, a "non-eruptible" magmatic zone (i.e., a solidification front close to the carbonate wall-rocks) may form between the large magmatic bodies and the host rock (Marsh, 1995).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Etna (e.g. see Allard et al, 1991;Frezzotti et al, 2009;Chiodini et al, 2011). In these scenarios, the contribution of decarbonation to the CO 2 budget at Mt.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This is far beyond the accepted isotopic range of magmatic CO 2 , which is comprised between~−4‰ in the extensional volcanism of Pantelleria and −3 to 0‰ in the subduction-related volcanism of Vulcano Island (Capasso et al, 1997) He with average arc ratio (1.2 × 10 10 ; Sano and Williams, 1996) and average MORB ratio (2 × 10 9 ; Marty and Jambon, 1987) respectively. Chiodini et al, 2011). In addition, we note that our estimated range for abiogenic CO 2 in Tunisia (δ 13 C CO2 values between 0 and +4‰) is more positive than the estimated deep-CO 2 supply to groundwater systems of central (δ 13 C CO2~− 3‰; Chiodini et al, 2000) to northcentral Italy (δ 13 C CO2 from − 3 to +1‰; Frondini et al, 2008), where a crustally contaminated mantle has been proposed as the main source of abiogenic CO 2 .…”
mentioning
confidence: 86%